Adopsi Inovasi Kawasan Rumah Pangan Lestari oleh Kelompok Wanita Tani Pangan Sari di Desa Peguyangan Kangin, Denpasar Utara - FAUZI, LUKMAN; PUTRA, I GEDE SETIAWAN ADI; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Adoption of Kawasan Rumah Pangan Lestari Innovation by Pangan Sari W oman F arming G roup at Peguyangan Kangin village, North Denpasar Kawasan Rumah Pangan Lestari is a yard utilization model of friendly agriculture cultivation that designed for fulfilling the family food needs,  food diversification based of local resources, the future crops preservation, and people income enhancement to improve people welfare. The purposes of this research is to find out the Kawasan Rumah pangan Lestari adoption process and its level by using descriptive qualitative analisys and measuring the likert scale. The study found the adoption process is began from awareness, insterest, evalualuation, trial, confirmation and finally to adoption stage. The adoption level of  Kawasan Rumah Pangan Lestari innovation by Pangan Sari woman farming group classified to medium level with 65,5% from the maximum score. The research recommend the farmer to adopt the inovation in accordance with the technical guidance. In addition, the government and other stakeholders have to continue motivating their people to improve their welfare.